2016
DOI: 10.14740/jocmr2365w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Extensive Recurrence of Triple Negative Breast Cancer: Are Both Therapy and Cancer Biology the Culprit?

Abstract: Triple negative breast cancer (TNBC) comprises 17-20% of all breast cancers and is one of the most common breast cancers. The lack of therapy and failure of existing therapy has been a challenge for clinicians. Doxorubicin (DOX) is the first-line therapy, however, it has significant limitations. Rapid extensive recurrence with metastasis in any cancer has been a challenge for surgeons and medical oncologists. The challenge can be due to failure of therapy, drug resistance, or epigenetic changes. Here, we are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Of several subtypes of breast cancer, the most aggressive form is characterised by absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth receptor 2 (HER2) and designated as triple negative breast cancer (TNBC) [ 3 ]. The drug resistance and recurrence rate of TNBCs is very high and it accounts for 10–24% of all breast cancers [ 4 6 ]. Most alarmingly and unlike in US and Europe, TNBC is highly prevalent in Indian women at premenopausal stage (<35 year) when they are in the prime time of their reproductive life.…”
Section: Introductionmentioning
confidence: 99%
“…Of several subtypes of breast cancer, the most aggressive form is characterised by absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth receptor 2 (HER2) and designated as triple negative breast cancer (TNBC) [ 3 ]. The drug resistance and recurrence rate of TNBCs is very high and it accounts for 10–24% of all breast cancers [ 4 6 ]. Most alarmingly and unlike in US and Europe, TNBC is highly prevalent in Indian women at premenopausal stage (<35 year) when they are in the prime time of their reproductive life.…”
Section: Introductionmentioning
confidence: 99%
“… Inflammation: Cardiotoxicity caused by DOX involves many factors, and the activation of pro-inflammatory mediators is one of the mechanisms leading to cardiomyocyte injury [ 34 ]. Studies have shown that the levels of inflammatory factors such as tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β) and interleukin-6 (IL-6) in DOX-administered rats were significantly increased [ [35] , [36] , [37] ]. DOX exposure stimulates the release of ROS and increases oxidative stress, thereby enhancing the expression of NF-κB in myocardial tissue, initiating an inflammatory cascade, and promoting the release of TNF-α and IL's [ 38 , 39 ].…”
Section: Analysis Of Journals and Cited Journalsmentioning
confidence: 99%
“…11 Several studies have shown that DOX therapy increases inflammation and IL-6 levels. 12,13 Evidence indicates that the extrinsic and intrinsic pathways of apoptosis are associated with DOXinduced cardiotoxicity. Caspase-3 plays a central role in the execution of apoptosis.…”
Section: Introductionmentioning
confidence: 99%